2020
DOI: 10.1109/access.2020.3013036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Intelligence and Semi-Empirical Methodologies for Estimation of Coverage in Mobile Networks

Abstract: To help telecommunication operators in their network planning, namely coverage estimation and optimisation tasks, this paper presents a comparison between a semi-empirical propagation model and a propagation model generated using Artificial Intelligence (AI). These two types of propagation models are quite different in their design. The semi-empiric Automatically Calibrated Standard Propagation Model (ACSPM) is specific for an operating antenna, being calibrated every time a use case application is used and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…To evaluate the model performance, and since a regression is used, the Mean Absolute Error (MAE) metric will be used, as it is the most common metric for regression. It measures the average absolute error between the real data and the estimated value, using (2) [37], where P rx is the real value,P rx is the estimated value, and N the number of samples.…”
Section: E Resultsmentioning
confidence: 99%
“…To evaluate the model performance, and since a regression is used, the Mean Absolute Error (MAE) metric will be used, as it is the most common metric for regression. It measures the average absolute error between the real data and the estimated value, using (2) [37], where P rx is the real value,P rx is the estimated value, and N the number of samples.…”
Section: E Resultsmentioning
confidence: 99%
“…Through the fitted curves, shown in Figure 6, it is possible to predict the G∆ (the difference between SISO and MIMO systems for a given BER performance), considering the variation in the R/P ratio. For the first iteration and considering a BER performance of 10 −2 the fitted curve is given by Equation (27). Equation (28) corresponds to a BER of 10 G∆ BER=10 −2 = 0.67 × ln (R/P) − 0.12;…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Note that this relationship is a function of the R/P ratio, so the higher this ratio the greater the impact. As an example, and according to Equation (27), for a BER of 10 −2 and the first iteration of IB-DFE, the value of E b /N 0 , improves by approximately 2.4 dB (G∆ = 2.4 dB), when moving from a SISO system to a MIMO system with 2 transmitting antennas and 10 receiving antennas (R/P = 5).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gathering and processing of such large quantities of information coming from these networks may be enabled by cloud services, which offer scal-able and elastic storage, processing and networking resources on-demand. In [5]- [9], it is demonstrated that the estimation of coverage within a SON context may gain from the use of cloud services. The large variety of different configuration parameters and Key Performance Indicators (KPIs) from cells using equipment from various manufacturers may be normalised thanks to a cloud-based infrastructure enabling their congregation and combination with large amounts of Drive Tests (DTs) to build accurate estimations of cell coverage.…”
Section: Introductionmentioning
confidence: 99%